Initial DWI and ADC imaging may predict outcome in acute disseminated encephalomyelitis: report of two cases of brain stem encephalitis. Issue 7 (16th June 2005) - Axer, H; Ragoschke-Schumm, A; Böttcher, J; Fitzek, C; Witte, O W; Isenmann, S
Abstract : Two young patients with acute disseminated encephalomyelitis (ADEM) of the brain stem are described. In spite of similar lesion sites in the brain stem, reaching from the upper medulla to the mesencephalon, the outcomes of the patients were very different: one made a full clinical recovery within three weeks while the other remained in a locked-in state more than a year after the disease episode. Both patients also differed in magnetic resonance imaging (MRI) findings on admission. The patient who remained in a locked-in state had pathological diffusion weighted imaging (DWI) scans and decreased apparent diffusion coefficient maps initially, with severe tissue destruction on follow up computed tomography, while the patient who recovered fully showed initially increased apparent diffusion coefficient values and almost complete resolution of MRI changes on follow up. Thus a comparison of these two cases may indicate differences in the underlying pathology in ADEM (vasogenic v cytotoxic oedema) that may be crucial for estimating tissue damage and clinical outcome.